Reinforcement of Unsupported Enamel by Restorative Materials and Dentin Bonding Agents: An In Vitro Study - M. Mirzaei; M. Ghavam; T. Rostamzadeh (Tehran University of Medical Sciences, 2010)
Objective: Preservation of unsupported occlusal enamel after removal of underlying carious dentin may result in maintenance of aesthetics as well as wear resistance against the opposing enamel. This study investigates the influence of different restorative materials and bonding agents on reinforcement of unsupported enamel in molars and compares it with sound dentin. Materials and Methods: In this in vitro study, forty- five extracted human molars were selected and randomly divided into five groups of nine. All lingual cusps were cut off. The dentin underlying the buccal cusps was removed in all groups except the positive control.The negative control group received no restorations. After application of varnish and Panavia F, spherical amalgam (Sina) and after application of Single-Bond (3M), composite resin (Tetric Ceram) was used to replace missing dentin. All specimens were thermocycled, then mounted in acrylic resin using a surveyor. Lingual inclination of facial cusps was positioned horizontally. Load was applied by an Instron machine at a crosshead speed of 10 mm/min until fracture. Data were subjected to ANOVA (one way) and Post hoc Test (Duncan). Results: Statistically significant differences were found between the five groups (P<0.001); however, no significant difference was revealed between bonded amalgam and the positive control groups (P=0.762). Composite and amalgam had the same effect (P=0.642), while the composite and negative group had no significant difference (P=0.056). Conclusion: Bonded amalgam systems (Panavia F) could reinforce the undermined occlusal enamel effectively.